A prototype of domestic internet filtering tools / Netty Akmal Borhan - Borhan, Netty Akmal (2006)
Enjoying the beauty of today's Internet landscape requires a greater degree of security and responsibility than a few years ago. Children are often introduced to the Internet at an early age, at which time the parent has full control over their child's Internet use. As the child develops however, parents naturally have to gradually relinquish this control, whilst at the same time doing all they can to keep their children safe form the dangers that the Internet poses. An Internet Filtering is a kind of software program that prevents one from viewing objectionable material on the Internet. ‘A prototype of Domestic Internet Filtering’ was developing for parents to control over their children’s behavior while surfing to the Internet. Its simply lists all request websites in a home network and. Furthermore, parents can check the entire request checklist and have a power to block certain websites that are not allowed. This project is developed specially for non-expertise computer parents and also focuses on Malaysian environments.